Evaluation of a "Picture Assisted Illustration Reinforcement" (PAIR) System for Oral Hygiene in Children with Autism: A Double-Blind Randomized Controlled Trial - Atrey J. Pai Khot; Abhra Roy Choudhury; Anil V. Ankola; Roopali M. Sankeshwari; Vinuta Hampiholi; Mamata Hebbal; Sagar Jalihal; Ram Surath Kumar; Laxmi Kabra; Sree Lalita Kotha (MDPI AG, 2023)
This study evaluated the potential of a novel pre-validated "Picture Assisted Illustration Reinforcement" (PAIR) communication system and conventional verbal techniques for Oral Health Education (OHE) in terms of dentition status, gingival health, oral hygiene status, and practices in 7- to 18-year-old children with Autism Spectrum Disorder (ASD). A double-blind randomized controlled trial was undertaken in a school for children with autism from July to September 2022. A total of 60 children were randomly assigned into two groups: a PAIR group (n = 30) and a Conventional group (n = 30). Cognition and pre-evaluation of all the children were assessed by standardized scaling measures. A pre-validated closed-ended questionnaire was administered to caregivers of both groups. At a 12-week post-intervention, a clinical examination was performed using the World Health Organization (WHO) Oral Health Assessment form 2013, gingival and Oral Hygiene Index Simplified (OHI-S). The gingival scores in the PAIR group (0.35 ± 0.12) exhibited a statistically significant decline in scores as compared to Conventional group (0.83 ± 0.37), p = 0.043. Meanwhile, the oral hygiene scores in the PAIR group and Conventional group were 1.22 ± 0.14 and 1.94 ± 0.15, respectively (p < 0.05). A significant improvement in oral hygiene practices was observed in the PAIR group. Incorporating the PAIR technique resulted in significant progress in child cognitive ability and adaptive behavior, which reduced gingival scores and improved oral hygiene scores, consequently improving oral hygiene practices among children with ASD.